Plasticity of Scarpa’s Ganglion Neurons as a Possible Basis for Functional Restoration within Vestibular Endorgans - Travo, Cécile; Gaboyard-Niay, Sophie; Chabbert, Christian (Frontiers in Neurology, 2012)
In a previous study (Brugeaud et al., 2007), we observed spontaneous restoration of the vestibular function in young adult rodents following excitotoxic injury of the neuronal network of vestibular endorgans. The functional restoration was supported by a repair of synaptic contacts between hair cells and primary vestibular neurons. This process was observed in 2/3 of the animals studied and occurred within five days following the synapse insult. To assess whether structural plasticity is a fundamental trait of altered vestibular endorgans and to decipher the cellular mechanisms that support such a repair process, we studied the neuronal regeneration and synaptogenesis in co-cultures of vestibular epithelia and Scarpa’s ganglion from young and adult rodents. We demonstrate that under specific culture conditions, primary vestibular neurons from young mice or rats exhibit robust ability to regenerate nervous processes. When co-cultured with vestibular epithelia, primary vestibular neurons were able to establish de novo contacts with hair cells. Under the present paradigm, these contacts displayed morphological features of immature synaptic contacts. This reparative capacity remained in older mice although to a lesser extent. Identifying the basic mechanisms underlying the repair process may provide a basis for novel therapeutic strategies to restore mature and functional vestibular synaptic contacts following damage or loss.